2023
DOI: 10.1111/jsr.13817
|View full text |Cite
|
Sign up to set email alerts
|

The trajectories and associations of insomnia symptoms with addictive behaviours in adolescents: A two‐year longitudinal study

Abstract: Summary Insomnia displays heterogeneous trajectories across adolescence, which may induce addictive behaviours, including internet gaming disorder and substance use. This study aimed to investigate the latent trajectory classes of insomnia symptoms over 2 years and to examine the associations between insomnia trajectories and these addictive behaviours. Participants were 910 adolescents from six middle schools in Shanghai, China (52.7% males; mean age = 13.17 years). The three‐wave survey measured insomnia sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Furthermore, the visual investigation of the funnel plot showed that this result was not affected by publication bias (Egger's test, p = .89). Regarding the studies not included in the meta-analysis, one confirmed these results ( Liu et al., 2023 ), while the other ( Wong et al., 2015 ) showed no association between insomnia symptoms and externalizing symptoms over time.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, the visual investigation of the funnel plot showed that this result was not affected by publication bias (Egger's test, p = .89). Regarding the studies not included in the meta-analysis, one confirmed these results ( Liu et al., 2023 ), while the other ( Wong et al., 2015 ) showed no association between insomnia symptoms and externalizing symptoms over time.…”
Section: Resultsmentioning
confidence: 57%
“…Furthermore, the visual investigation of the funnel plot showed that this result was not affected by publication bias (Egger's test, p = .89). Regarding the studies not included in the metaanalysis, one confirmed these results (Liu et al, 2023), while the other (Wong et al, 2015) showed no association between insomnia symptoms and externalizing symptoms over time.…”
Section: The Interplay Between Sleep and Externalizing Symptomsmentioning
confidence: 57%